Make it the same : poetry in the age of global media - Edmond, Jacob (Literature Now., 2019)
"In Make It the Same, Jacob Edmond argues that literary change in our age of globalization and digital media is best understood as the process of reframing, remediating, and recontextualizing existing literary and artistic works as opposed to privileging "innovative" or "original" works. Edmond examines how writers over the past fifty years have employed appropriation and media technologies -- tape recorders and typewriters (carbon copies), the Internet and machine-based writing -- as a way to develop new modes of creation and distribution. In looking at examples from a wide range of literatures - Caribbean, Soviet, American, and Chinese - Edmond reveals how copying practices in contemporary poetry have drawn on existing material to challenge and undermine cultural authority by questioning the privileging of conventional understandings of originality. While recognizing the liberatory potential of these practices, Edmond also considers how, in recent years, these practices have been seen to reinforced certain social and racial hierarchies"--